Mineralogical Characterization of Pegmatites with Occurrences of Halloysite in the Regions of Porciúncula (RJ) and Patrocínio do Muriaé (MG), Southeastern Brazil - Licursi, Ernesto Adler; Bertolino, Luiz Carlos; da Silva, Francisco José (Anuário do Instituto de Geociências, 2023)
Halloysite (Al2Si2O5(OH)4.2H2O) is a polymorphic kaolinite mineral whose predominant morphology is tubular. Due to this characteristic, halloysite is widely used in industrial applications, such as manufacture of silica- luminous catalysts, used for industrial chemical reactions; French porcelain; and the cracking of petroleum fractions into gasoline. Halloysite also has potential as a nanomaterial, particularly as an ingredient in polymer nanocomposites and as active agent for medical, agricultural, and other uses. This clay mineral occurs in a wide variety of geological environments as a product of alteration of rocks rich in sodium and potassium feldspars, such as intrusive acid rocks, granites, anorthosites, and pegmatites. This article characterizes halloysite and describes the treating process of kaolin- halloysite samples from four pegmatites, located in Porciúncula (Rio de Janeiro State) and Patrocínio do Muriaé (Minas Gerais State). The samples of the studied pegmatites were treated for mineralogical characterization and analyzed by X-ray diffractometry and scanning electron microscopy. Density, granulometry, and visual appearance of the grains were also analyzed. The samples were found to be composed of kaolinite/halloysite, feldspar, quartz, biotite, goethite and muscovite. Using X-ray diffractometry, gibbsite were also identified in one sample. With the results presented here, the two regions can be possible targets for researching halloysite deposits in the states of Rio de Janeiro and Minas Gerais.